HEALTH POLICY ANALYSIS: IMPLEMENTATION OF SELF-ISOLATION POLICY COVID-19 PATIENT IN CIKARANG COMMUNITY BEKASI REGENCY - Emmelia Kristina Hutagaol (Gorontalo State University, 2022)
AbstractThe pandemic of Severe Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) that also known as COVID19 has brought a lot of losses, in terms of morbidity due to exposure to the virus and mortality, and the spread are so fast including at Bekasi Regency. The triangle of disaster management is the existence of government regulation, community participation and business involvement. The participation of health community representing the business involvement. To accelerate the response for this pandemic, the government makes policies and rules ranging from laws, regulations from Ministry of Health of Republic Indonesia to standard operating procedures that imposed by hospital and public health center. This research took data at Bekasi Regency West Java with qualitative data collection methods and an analytical descriptive research design. The data collection methods were in the form of in-depth interviews form stakeholders including confirm COVID-19 patients who had discharged form RSSM Hospital. The respondents from hospital were hospital director, nurses, and hospital administrators. The respondents from public health centre were surveillance officers. The patients with coronavirus including post-hospitalization and those who underwent self-isolation were confirmed by medical record from hospital. The result showed that monitoring of self-isolation cases was only for new cases found by the public health center, or we called Puskesmas but not post-hospitalized patients who were sent home to continue treatment at home.Keywords: Community participation; Discharge planning; Health policy; Role of health workers; Self-isolation